Introduction to Epidemiology and Control of Peste des Petits Ruminants (Eco-PPR) tools. 6.1 Flock Dynamics―Overview - Wieland, Barbara; Dione, Michel M.; Okoth, Edward A.; Jones, B.; Kotchofa, Pacem; Ilboudo, Guy S.; Campbell, Zoë A.; Rutto, Erick (International Livestock Research Institute, 2020)
Flock dynamics affects vulnerability to different diseases.